Editorial: Present and future of peer review and scientific publishing in Law - perspectives from the Brazilian Journal of Criminal Procedure data in 2017 and the views of its authors and reviewers - Vinicius Gomes de Vasconcellos (Revista Brasileira de Direito Processual Penal)
Based on the statistics and projects implemented in the Brazilian Journal of Criminal Procedure and data obtained from research conducted with authors and reviewers, this editorial intends to analyze aspects of peer review and the scenario of Law scientific production in journals. In this sense, the information presented reinforces the importance of an editorial project based on seriousness, publicity and transparency, with the adoption of an active posture by the editors, recognition of the reviewers, as well as consolidation of corrections rounds system and the authors' duty to respond to it.